Penerapan Model PBL dengan Pendekatan Culturally Responsive Teaching Untuk Meningkatkan Hasil Belajar Matematika - Akmal, Regi Akmal Fauzan; Muhammad Ade Irawan; Muhamad Gazali; Zulfiana Hauli (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This study aims to improve students' mathematics learning outcomes by implementing the Problem Based Learning model with a Culturally Responsive Teaching approach. The subjects of the study were 32 eighth-grade students from SMP Negeri 1 Labuhan Haji, Lombok Timur. The research used a classroom action research (CAR) method conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The results showed a significant improvement in learning outcomes from the pre-cycle to cycle I and cycle II. In the pre-cycle, only 15.63% of students achieved mastery, with an average score of 52.96. After the implementation of the Problem Based Learning model with a Culturally Responsive Teaching approach in cycle I, the mastery percentage increased to 59.38% with an average score 67,97, and in cycle II, it reached 87.50% with an average score of 85.10. Based on these results, it can be concluded that the implementation of the Problem Based Learning model with a Culturally Responsive Teaching approach is effective in improving students' mathematics learning outcomes.